An assessment of service quality gap in farmer producer organizations: A comparative approach using SERVQUAL - Shanmuga Priya, K; Selvam, S; Parimalarangan, R; Murugananthi, D; Jeyaprakash, P; Jona, I P (Plant Science Today, 2025)
This study examines service quality gaps in Farmer Producer Organizations (FPOs) in Tamil Nadu using the SERVQUAL model by comparing Grade A and Grade D FPOs. Data were collected through a stratified random sampling method from 240 members across four FPOs to assess five key service quality dimensions. The findings revealed significant service gaps with Grade D FPOs showing larger service quality gaps particularly in tangibles (-1.21), reliability (-1.32) and empathy (-1.17). These gaps disclose shortcomings in infrastructure, timeliness of service delivery, accuracy in record keeping and member focused engagement. In contrast, Grade A FPOs demonstrated narrower gaps, indicating stronger operational efficiency and higher levels of member satisfaction. The pronounced service quality gaps in Grade D FPOs pose threat to member trust, active participation and the long-term sustainability of these organizations. The study recommends targeted policy interventions such as the implementation of standardized service delivery protocols and workforce training. Bridging these gaps is critical to strengthening the role of FPOs as vital institutions for promoting inclusive and sustainable growth in Indian agricultural sector.